PEMEROLEHAN BAHASA ANAK USIA 3 TAHUN : TINJAUAN FONOLOGI - Wita Dwi Payana (Jurnal Bahastra, 2020)
This study aims to determine the acquisition of phonology in a 3-year-old child named Aqila Shafa. The results showed that the acquisition of the phoneme /r/ which turned into /l/ from the data submitted (conversations 1 and 2), and the acquisition of the phoneme /s/ which turned into /c/ from the data submitted (conversations 3 and 4). The process of language acquisition is also influenced by the role of the family as an intermediary for a child's understanding of his first language.